Challenges and Opportunities of Inclusive Education in Islamic Higher Education Institutions: A Case Study in Indonesia - Khaeroni Khaeroni; Fithri Meiliawati; Roudhotul Jannah (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This study explores the challenges and opportunities in implementing inclusive education in Indonesia’s Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam/PTKI). Inclusive education, which seeks to ensure access and equity for students with disabilities or special needs, has become increasingly relevant within Islamic higher education as part of the broader agenda for educational equity and human rights. The study employs a qualitative approach with a case study design involving interviews, observations, and documentation at several PTKIs that have initiated inclusive education programs. Findings reveal that PTKIs face several challenges, including a lack of institutional policy, inadequate infrastructure, limited teaching competencies in inclusive pedagogy, and socio-cultural barriers stemming from stigmatisation. However, the study also identifies key opportunities, such as aligning inclusive values with Islamic teachings, institutional commitment to equity, and the role of government policies in supporting inclusivity. Though facing substantial barriers, the study concludes that inclusive education in PTKIs can be significantly enhanced through policy reforms, capacity building, and collaboration across institutional and governmental levels. These findings contribute to the growing discourse on inclusive education in Islamic contexts and provide practical implications for educational leaders and policymakers